(untitled) - Thacker, J.R.M (Cambridge, 2002)
An Introduction to Arthropod Pest Control provides an up-to-date, detailed overview of current approaches to pest control including chemical and biological pest control and the latest developments in biotechnology. The book specifically emphasises the techniques available for controlling pests and is intended as a standard introductory text for undergraduates, postgraduates, and professional pest control practitioners.
Keywords: Động vật chân đốt,Arthropod pests; Điều khiển,Control